Enterprise Social Networking and Innovation in the Service Industry: A Mixed Methods Study - Rahman, Naseem Jahan (Auckland University of Technology, 2021)
With the significant growth in the service sector in recent years, researchers are paying increasing attention to the co-creation and application of knowledge in service innovation. Knowledge sharing is a key driver of service innovation, as it encourages decisions to apply knowledge into products, services, and organisational designs. The emergence of social media technologies, especially enterprise social networking (ESN), has made knowledge sharing easier, but has also led to some adverse outcomes. These adverse outcomes include but are not limited to: low productivity, interpersonal conflict, and the possibility of leaking sensitive information to external parties. Two research problems are examined in this study: the low acceptance of ESN by employees, because of the fear that they jeopardise their status by sharing knowledge; and the inappropriate use of ESN, as seen in an increase in interpersonal conflicts or the leaking of information outside the organisation. This study aims to understand how knowledge sharing through ESN can influence innovation in the service industry, and how the strength of this relationship is affected by the governance of ESN. Therefore, the research question addressed in this study is: How can organisations encourage employees to use ESN for knowledge sharing to enhance their innovation outcomes? As the phenomenon of using ESN for knowledge sharing for innovation is a novel area of research, this study used a two-phase sequential mixed methods design. The first phase was a qualitative study (using interview data) that evaluated a conceptual model, which relates ESN for knowledge sharing to service innovation and governance. The second phase is a quantitative study (using survey data), where the relationships between these constructs are statistically examined. The qualitative study was conducted by interviewing 11 participants from banks and investment firms located in New Zealand. For the quantitative study, 104 global participants from the financial industry were surveyed. The interviews revealed that: a) innovation and knowledge sharing are related to developing new products/services or improving existing ones; b) different ESN tools used for knowledge sharing complement each other; e) an open and trusted environment enhances knowledge sharing using ESN, which in turn fosters innovation, and f) users are aware of their organisation’s policies and standards for sharing knowledge, including those related to social media. The quantitative study revealed that ESN for knowledge sharing is significantly related to service innovation. Further, the findings suggest that, although trust has a direct effect on service innovation, the use of ESN for knowledge sharing partially mediates the relationship between trust and service innovation. The results also reveal that governance significantly moderates the relationship between ESN for knowledge sharing and innovation. This study has both theoretical and practical implications. Theoretically, this paper provides insights into the relationship between trust, knowledge sharing and innovation. Further, the study also demonstrates the role of governance in mitigating the negative aspects of ESN implementation (low acceptance and inappropriate use of ESN), so that they do not outweigh its benefits. The practical implications of this study are that senior executives of firms that are using or intending to use ESN for knowledge sharing should: a) keep track of the evolving nature of ESN and see how it can best enhance knowledge sharing, and b) develop an open culture in their organisations to promote knowledge sharing and social relationships among employees, in addition to implementing ESN applications.
Keywords: Service innovation; Enterprise social networking; Knowledge sharing; Trust; Governance